Assessment of Flow through Microchannels for Inertia-Based Sorting: Steps toward Microfluidic Medical Devices - Rucha Natu; Suvajyoti Guha; Seyed Ahmad Reza Dibaji; Luke Herbertson (Micromachines, 2020)
The development of new standardized test methods would allow for the consistent evaluation of microfluidic medical devices and enable high-quality products to reach the market faster. A comprehensive flow characterization study was conducted to identify regulatory knowledge gaps using a generic inertia-based spiral channel model for particle sorting and facilitate standards development in the microfluidics community. Testing was performed using 2–20 µm rigid particles to represent blood elements and flow rates of 200–5000 µL/min to assess the effects of flow-related factors on overall system performance. Two channel designs were studied to determine the variability associated with using the same microchannel multiple times (coefficient of variation (CV) of 27% for Design 1 and 18% for Design 2, respectively). The impact of commonly occurring failure modes on device performance was also investigated by simulating progressive and complete channel outlet blockages. The pressure increased by 10–250% of the normal channel pressure depending on the extent of the blockage. Lastly, two common data analysis approaches were compared—imaging and particle counting. Both approaches were similar in terms of their sensitivity and consistency. Continued research is needed to develop standardized test methods for microfluidic systems, which will improve medical device performance testing and drive innovation in the biomedical field.